Pejabat Tanah Dan Jajahan Pasir Puteh Kelantan / Ku An Nur Aifa Ku Hasan - Ku Hasan, Ku An Nur Aifa (Universiti Teknologi MARA, Perlis, 2023)
Pejabat Tanah Dan Jajahan Pasir Puteh Kelantan represents a governmental institution. The establishment which is also known as PTJPP is a land registry office located in Pasir Puteh. The colonial administrator at PTJPP serves as both the governing authority responsible for policy formulation and implementation, as well as Pasir Puteh’s main source of information. It acts as the major planner of Colony development, the coordinator of Colony development implementation, the Colony housing agent, the liaison of the government tongue, and the driver of an excellent administrative system and a good work culture at the Colony level. Pejabat Tanah dan Jajahan Pasir Puteh Kelantan has been divided into several departments which are Unit Pentadbiran, Unit Pembangunan, Unit Hasil, Unit Pendaftaran and Unit Tanah. Each unit performs a distinct purpose. This is to make sure that every planned event goes off without a hitch. To do this, an organization's plans need to be set up so that each goal can be met. PTJPP has a number of strategies, such as leadership development, legislation, and meetings. Other strategies include improving relationships between heads of organizations at the Colony level, increasing cooperation between departments within the Colony, forming working committees, putting human development at the top of the list and putting an emphasis on it, increasing appreciation for quality and a good work culture, and developing the organization as a whole.